2008
DOI: 10.1055/s-2008-1066673
|View full text |Cite
|
Sign up to set email alerts
|

Iloprost, ein stabiles Prostacyclinderivat, bei arterieller Verschlußkrankheit im Stadium IV: Eine placebo-kontrollierte Multizenterstudie

Abstract: The effectiveness of iloprost, a prostacyclin derivative, was assessed in a placebo-controlled multicentre trial on 101 patients with chronic arterial disease, stage IV. All patients were on a basic local treatment, 53 randomly being assigned to the iloprost group, 48 to the placebo one. Both groups received identical saline infusions, one with the other without iloprost. Infusions were given on 28 consecutive days, iloprost being added at a dose of up to 2 ng/kg.min over six hours. At the end of the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Prostaglandin E1 has been administered in various dosing schedules, for example, 60 to 80 micrograms over 2 to 4 hours per day and iloprost in doses of 0.5 to 2 ng per kg per min over 6 hours each day. The majority of studies have found that parenteral administration of either PGE-1 or iloprost reduced pain, as assessed by analgesic consumption, ulcer size, and/or amputation (1,(528)(529)(530)(531)(532)(533)(534)(535)(536). The largest of these trials was conducted by the Ischemia Cronica degli Arti Inferiori study group and comprised 1560 patients with CLI.…”
Section: (Level Of Evidence: B)mentioning
confidence: 99%
“…Prostaglandin E1 has been administered in various dosing schedules, for example, 60 to 80 micrograms over 2 to 4 hours per day and iloprost in doses of 0.5 to 2 ng per kg per min over 6 hours each day. The majority of studies have found that parenteral administration of either PGE-1 or iloprost reduced pain, as assessed by analgesic consumption, ulcer size, and/or amputation (1,(528)(529)(530)(531)(532)(533)(534)(535)(536). The largest of these trials was conducted by the Ischemia Cronica degli Arti Inferiori study group and comprised 1560 patients with CLI.…”
Section: (Level Of Evidence: B)mentioning
confidence: 99%
“…The majority of studies have found that parenteral administration of either PGE-1 or iloprost reduced pain, as assessed by analgesic consumption, ulcer size, and/or amputation (1,(528)(529)(530)(531)(532)(533)(534)(535)(536). The largest of these trials was conducted by the Ischemia Cronica degli Arti Inferiori study group and comprised 1560 patients with CLI.…”
Section: Critical Limb Ischemia and Treatment For Limb Salvagementioning
confidence: 99%